2019
DOI: 10.1016/j.chembiol.2019.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Covalent CDK14 Inhibitors with Pan-TAIRE Family Specificity

Abstract: Highlights d A covalent, cell-permeable inhibitor of CDK14 was developed d Methods for assessing cellular engagement of TAIRE family kinases are described d Kinase motif analysis and phospho-proteomics identified putative CDK14 substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Although our analysis failed to uncover selective modulators of these CDKs, the energy transfer-based probes developed in this work can be used to identify and optimize potential tool molecules for these understudied but important family members. Encouragingly, during the preparation of this manuscript a number of inhibitors were reported for understudied CDKs including the TAIRE subfamily 60 as well as CDK11 61 . As our compound panel represents only a fraction of known CDKi's, the results presented here suggest that comprehensive assessments of CDK target engagement are warranted as a standard practice for all novel tool compounds and promising clinical leads that are beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although our analysis failed to uncover selective modulators of these CDKs, the energy transfer-based probes developed in this work can be used to identify and optimize potential tool molecules for these understudied but important family members. Encouragingly, during the preparation of this manuscript a number of inhibitors were reported for understudied CDKs including the TAIRE subfamily 60 as well as CDK11 61 . As our compound panel represents only a fraction of known CDKi's, the results presented here suggest that comprehensive assessments of CDK target engagement are warranted as a standard practice for all novel tool compounds and promising clinical leads that are beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…As kinases are typically druggable targets which can be inhibited in non-invasive ways ( 39 ), we next asked whether CDK14 pharmacological inhibition would be a tractable route for decreasing α-Syn levels. We used a recently developed CDK14 covalent inhibitor (FMF-04-159-2) ( 26 ) to test whether acute depletion of CDK14 decreased α-Syn levels. We found that in HEK293T cells, CDK14 inhibition induced a strong reduction in endogenous α-Syn protein levels ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Its expression is upregulated in certain cancers, such as esophageal and colorectal cancer, for which it has generated attention as a therapeutic target ( 24 , 25 ). In fact, this has led to the recent development of FMF-04-159-2, a potent, covalent inhibitor of CDK14 ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…When examining CCNY:Cdk14, a membrane complex linked to Wnt signaling whose peak expression is thought during M phase [12,[67][68][69], Cdk14 overexpression without its CCNY regulator was found to correspond indirectly with proliferation gene expression and directly with co-expression of hedgehog signaling and epithelial to mesenchyme transition (EMT) genes, in COAD and most LUAD. The few COAD with Cdk14 mutations appeared to reverse the heatmap expression patterns for proliferation, hedgehog signaling, and EMT components.…”
Section: Discussionmentioning
confidence: 99%